Case Study of AGV in Industry 4.0 Environments - An Evaluation of Wireless Communication Protocols - Kampen, Anne-Lena; Cupek, Rafal; Fojcik, Marcin; Drewniak, Marek; Ovsthus, Knut (Conference proceedings - IEEE International Conference on Systems, Man, and Cybernetics, 2022)
The new manufacturing paradigm, which is organized under Industry 4.0, has strict requirements for supporting technologies. Wireless communication technology should be available to support movable nodes and to make a production site flexible and able to adapt to the various requirements of the manufacturing operations and the production management systems. Depending on the application and processes being serviced, communication is subject to a broad range of strict requirements, from reliability and predictable delays to low cost and reduced energy consumption. In this paper, we present a real scenario in which Autonomous Guided Vehicles (AGVs) equipped with Collaborative robots (Cobots) are used as transportation and production units, and therefore, a set of communication services must be implemented. The challenges associated with moving AGVs are discussed, and the associated requirements that apply to wireless communication are presented. The results allow to formulate a definition of a three-level hierarchy for communication services (onboard, shopfloor, and system) that are required to implement the Industry 4.0 paradigm. In addition, a review of the relevant wireless network protocols that can be used for the implementation of communication services is presented.